2022
DOI: 10.1017/ice.2022.40
|View full text |Cite
|
Sign up to set email alerts
|

Use of serial testing to interrupt a severe acute respiratory coronavirus virus 2 (SARS-CoV-2) outbreak on a hospital medical floor—Minnesota, October–December 2020

Abstract: Objective: Describe a SARS-CoV-2 hospital outbreak and the role of serial testing of patients and healthcare personnel (HCP) in interrupting transmission. Design: Outbreak investigation Setting: Medical floor of a tertiary care center in Minnesota Methods: Serial testing for SARS-CoV-2 and whole genome sequencing (WGS) of positive specimens from HCP and patients was used. An outbreak-associated case was defined as a positive SARS-CoV-2 molecular test i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…In this study, we have shown the benefits of the outbreak investigation of adding WGS analysis. Other reports have highlighted the utility of WGS in outbreak investigation, 3,5,9,12,13,16,18,20,21 including its ability to identify complex outbreaks characterized by introduction of infections by >1 source or refute the original transmission hypothesis. WGS supported this study's hypothesis of the introduction of SARS-CoV-2 onto the unit by 2 patients who presented to the hospital with respiratory symptoms, one of whom was later found to have had community contact with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we have shown the benefits of the outbreak investigation of adding WGS analysis. Other reports have highlighted the utility of WGS in outbreak investigation, 3,5,9,12,13,16,18,20,21 including its ability to identify complex outbreaks characterized by introduction of infections by >1 source or refute the original transmission hypothesis. WGS supported this study's hypothesis of the introduction of SARS-CoV-2 onto the unit by 2 patients who presented to the hospital with respiratory symptoms, one of whom was later found to have had community contact with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Since the beginning of the coronavirus disease 2019 (COVID-19) pandemic, 1 there have been reports of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) transmission to patients and healthcare workers (HCW) within healthcare facilities. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Factors contributing to these outbreaks have included patient accommodation in multibed rooms or bays, [6][7][8]11,12,17 lack of infection prevention and control precautions due to failure to identify patients admitted with or incubating SARS-CoV-2, [6][7][8][9][10]20 and nosocomial exposure to a patient with COVID-19. [15][16][17][18][19][20] Rhee et al 22 demonstrated that consistent application of infection prevention and control measures can reduce or prevent the spread of SARS-CoV-2 in healthcare settings.…”
mentioning
confidence: 99%
“…This is consistent with other short-term asymptomatic COVID-19 testing schemes in university and hospital settings. 19, 20 For example, in their study of weekly SARS-CoV-2 antigen testing in a university over a 6-week period, Bigouette et al . found weekly adherence ranged between 70·5% and 80·6%.…”
Section: Discussionmentioning
confidence: 99%
“…To the Editor— During the coronavirus-disease-2019 (COVID-19) pandemic, in-hospital surveillance via serial severe acute respiratory coronavirus virus 2 (SARS-CoV-2) testing has repeatedly demonstrated its utility in early detection, isolation, and interruption of nosocomial transmission. 1 However, analytical sensitivity of real-time, reverse-transcriptase, polymerase chain reaction (rRT-PCR) testing for SARS-CoV-2 is crucial in ensuring accurate results and early detection of COVID-19 cases and, thus, to mitigate nosocomial COVID-19 outbreaks. The emergence of SARS-CoV-2 variants has been demonstrated to negatively affect analytical sensitivity of rRT-PCR assays.…”
mentioning
confidence: 99%
“…The risk of an HCW acquiring COVID-19 from another HCW is reportedly 3 times higher than contracting it from patients. 1 Given that not all infections are detected, it is critically important that during surges, all infection controls (administrative, engineering, and personal protective equipment [PPE]) are optimized to protect patients and HCW colleagues. 2 We report a case in which a highly infectious HCW working with profoundly immunosuppressed patients did not transmit SARS-CoV-2 to patients despite multiple close interactions.…”
mentioning
confidence: 99%